KORELASI KARAKTERISTIIK PASIEN DENGAN DRUG RELATED PROBLEMS PASIEN STROKE ISKEMIK GERIATRI DI RS X KABUPATEN TULUNGAGUNG - Dhanang Prawira Nugraha; Antonius Adji Prayitno Setiadi; Yosi Irawati Wibowo (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Drug related problems (DRP) can cause problems in treatments of patients with ischemic stroke.Objective: This study was to determine the correlation between the characteristics of patients with ischemic stroke and the DRP.Methods: A population in this study was 53 patients at dr Iskak Public Hospital in Tulungagung. Inclusion criteria were patients who were = 60 years old and were diagnosed as acute ischemic stroke patients. The DRP was classified based on Pharmaceutical Care Network Europe version 6.2, especially problem and cause domain. Correlation between age, duration of treatment, number of comorbidities and number of drugs and the DRP was analysed by Spearman Rho or by Pearson analysis. The relationship between gender, guaranteed care and the DRP was analysed by using Eta analysis.Results: This study revealed that patients with 60-69 years were 24 patients (45.28%), men were 30 patients (57%), 1 comorbidity was 26 patients (49.06%), duration of 5 days was 14 patients (26.42%), BPJS patients were 23 patients (35.94%), using 6 types of drug was 11 patients (20.75%). Age, sex and care guarantee did not correlate with the DRP (p-values > 0.05). Duration of treatment, number of comorbidities and number of drugs correlated with the DRP (p-value <0.05) with consecutive correlation strength: weak (R = 0.32), moderate (R = 0.45), strong (R = 0.56).Conclusion: Duration of treatment, number of comorbidities and number of drugs correlated with increasing incidences of the DRP in geriatric ischemic stroke patients.